Hubungan Antara Sikap Kerja Dan Masa Kerja DenganGangguan Fungsional Nyeri Punggung Bawah PadaPekerja Tenaga Panggul - Setyawan, Muhammad Fery; , Wahyuni, S.Fis., M.Kes (2016)
Background: One of the factors of low back pain (LBP) experienced labor force working attitude pelvis is unnatural cause the body moved against the natural or adoptive-transport activities manually backs are bent and twisted bodies. Another factor that is a working tool and a work station that does not match the capabilities and limitations of the workers will trigger the occurrence of musculoskeletal complaints Objective: This study was conducted to determine the relationship between working attitude and working life with a functional disorder of lower back pain in the pelvis power workers Benefits Research: For information on working in the Bulog Krikilan Masaran District of Sragen work being undertaken potentially lead to musculoskeletal disorders, one of which is lower back pain so that workers can anticipate and take steps to prevent as well as improvements in the workplace. Methods: The study observational analytic research with cross sectional approach. The sampling technique used purposive sampling, as many as 50 respondents. Measuring instrument research using questionnaire. The statistical test used was chi-square. Results: Statistically relationship work attitude with a functional disorder of lower back pain showed a p-value of 8.887 or probability (significance) <0.05. For the past relationship working with a functional disorder of lower back pain showed a p-value of 16.128 or probability (significance)> 0.05. Conclusion: There was a significant correlation between working attitude and working life with functional disorders nyari lower back at the pelvis power workers in Bulog Krikilan Masaran District of Sragen with interview and questionnaire